A proximidade discursiva nas cartas dos romances A correspondência de Fradique Mendes, de Eça de Queiroz e Nação crioula: A correspondência secreta de Fradique Mendes, de José Eduardo Agualusa - Lima, Daniela de Oliveira [UNESP] (2015)
The presence of Eça de Queiros both in Portuguese Literature as the Brazilian was always outstanding, fact that even today remains active in the reception of his literary production by contemporary writers. This dissertation focuses on two works that brings in common the character Carlos Fradique Mendes. The basic texts for the approximation between the letters were A Correspondência de Fradique Mendes, one of the last works of the Portuguese writer, and a contemporary novel Nação Crioula: a correspondência secreta de Fradique Mendes, by the Angolan Jose Eduardo Agualusa. The motivations for the development of the research arose from interest in working with works of different historical and social contexts, attempt to show the relations between the two spaces that, to comprise the borders are capable of approaching, once Angola and Portugal have historical relations as a result of the colonization. And we still choose to verticalize the study in the letters that compose the narratives. The main points for the development of this paper were backed in theories about the Comparative Literature, intertextuality, parody, among others, without leaving aside the social context of Portuguese Literature and in the case of Angola, of the African Literature in Official Portuguese language. Our reflections along the way demonstrated that the character created by Eça de Queiros, Antero de Quental and Jaime Batalha Reis still remains present in the reader‟s imaginary, we conclude the present study shows how the texts have discuss among themselves, even with over the years. The research also contributes to the queirosean legacy, as well as for those interested in the study of African literatures in Portuguese Language, that follows arousing the interest of readers and contemporary researchers